Enhancing Digital Competence: A Comprehensive Digital Educational Games Training Needs Analysis for PAUD Teachers - Nurhayati, Sri; Novianti, Dini (Jurnal Smart Paud, 2024)
This study assesses the digital competencies and training needs of early childhood education (PAUD) teachers in Kecamatan Batujajar, West Bandung Regency. emphasizing their use of digital educational games. A survey was conducted to evaluate teachers' skills and confidence with computer technologies and educational software. Results indicate a significant gap in digital literacy; most teachers lack fundamental computer skills and familiarity with digital tools, despite acknowledging their benefits for enhancing student engagement. This research advocates for targeted digital literacy training tailored to early childhood educators, focusing on both technical skills and pedagogical methods for effective technology integration. The study also recommends ongoing professional development to help teachers overcome technological barriers. This work is novel in pinpointing the specific digital adoption challenges faced by PAUD teachers and suggests focused training programs to enhance their digital capabilities, which is crucial for improving educational outcomes.